Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Garam: Studi kasus pada Perempuan Penjual Garam di Daerah Pesisir Jeneponto - Kapriani Kapriani; Andi Hendra Syam; Ikhsan Amar Jusman; Nuzul Fadilah; Rahmat Fauzi (Al-Buhuts, 2025)
The purpose of this study is to analyse the appropriate marketing strategies to increase salt sales. This study was conducted in the coastal area of Nasara, Bangkala District, Jeneponto. The type of research is descriptive qualitative research. Data collection was carried out through interviews with respondents who were the main informants in this study. The population in this study were women salt sellers along the coast of Nasara, Jeneponto Regency. The sampling method used purposive sampling with a sample size of 15 respondents. Data analysis used the IFAS, EFAS and SWOT analysis techniques. The results of the analysis included the S-O Strategy, which is to utilise the local image as a salt production centre through local branding, affordable prices, digital promotion, partnerships with local businesses, and capacity building through government training programmes. The W-O Strategy involves overcoming weaknesses through processing and packaging training, business assistance for PIRT permits, establishing cooperatives, utilising modern and traditional distribution channels, providing attractive kiosks, and digital media-based promotion. The S-T Strategy involves maintaining the quality and authenticity of local salt, building customer loyalty, and managing supplies to anticipate price fluctuations and seasonal changes. The W-T strategy involves forming cooperatives to overcome capital and distribution constraints, diversifying products, and developing emergency production plans with warehouse storage support.